Answer:
The answer to your question is below
Step-by-step explanation:
Side 1: 3x² - 2x - 1
Side 2: 9x + 2x² - 3
Perimeter: 5x³ + 4x² - x - 3
a) Length of side 1 and side 2
Length = (3x² - 2x - 1) + (9x + 2x² - 3)
= 3x² - 2x - 1 + 9x + 2x² - 3
= (3x² + 2x²) + (-2x + 9x) + (-1 - 3)
= 5x² + 7x - 4
b) Length of the third side
Third side = Perimeter - side 1 - side 2
Third side = 5x³ + 4x² - x - 3 - (5x² + 7x - 4)
Third side = 5x³ + 4x² - x - 3 - 5x² - 7x + 4
Third side = 5x³ + (4x² - 5x²) + (-x - 7x) + (-3 + 4)
Third side = 5x³ - x² - 8x + 1
c) Yes, in this problem we did both operations (addition and subtraction) and we can notice that the polynomials are closed. Also they follow the closure property the addition or subtraction of two polynomials gives another polynomial.
The answer to this problem is 9.15
Answer:
4
Step-by-step explanation:
theres only 4 to pick from
Answer:
2 right? 3 and -3?
Step-by-step explanation:
10/1 * 1/3 = 30/3
1 1/3 = 4/3
4/3 can only go into 30/3, 7 times, with a remainder of 2/3.
7 2/3